Warship 2007 : the affordable warship - International Conference Warship 2007 : The Affordable Warship (20 - 21 June 2007 : Bath, UK); The Royal Institution of Naval Architects (Great Britain) (London, UK : The Royal Institution Of Naval Architects, 2007)
19